Plasma level of omentin-1, its expression, and its regulation by gonadotropin-releasing hormone and gonadotropins in porcine anterior pituitary cells - Natalia Respekta; Karolina Pich; Ewa Mlyczyńska; Kamil Dobrzyń; Christelle Ramé; Tadeusz Kamiński; Nina Smolińska; Joëlle Dupont; Agnieszka Rak (Scientific Reports, 2023)
Abstract Omentin-1 (OMNT1) is an adipokine involved in the regulation of energy metabolism, insulin sensitivity, and reproduction. The present study was the first to investigate the plasma levels and expression of OMNT1 in the anterior pituitary (AP) gland on days 2–3, 10–12, 14–16, and 17–19 of the estrous cycle of normal-weight Large White (LW) and fat Meishan (MS) pigs. Next, we determined the effect of GnRH, LH, and FSH on the OMNT1 levels in cultured AP cells. The gene and protein expression of OMNT1 in AP fluctuated during the estrous cycle, with a higher expression in MS than in LW (except on days 10–12). However, plasma levels of OMNT1 were higher in LW than in MS. OMNT1 was localized in somatotrophs, lactotrophs, thyrotrophs, and gonadotrophs. In LW pituitary cells, GnRH and gonadotropins stimulated OMNT1 protein expression (except FSH on days 14–16) and had no effect on OMNT1 levels in the culture medium. In MS pituitary cells, we observed that GnRH and LH increased while FSH decreased OMNT1 protein expression. These findings showed OMNT1 expression and regulation in the porcine AP and suggested that OMNT1 could be a new player modifying the pituitary functions.